Evaluation of a new algorithm for tracking activation during atrial fibrillation using multipolar catheters in humans. - Mann, Ian; Coyle, Clare; Qureshi, Norman; Nagy, Szabolcs Z; Koa‐Wing, Michael; Lim, Phang Boon; Francis, Darrel P; Whinnett, Zachary; Peters, Nicholas S; Kanagaratnam, Prapa; Linton, Nick W.F. (Journal of Cardiovascular Electrophysiology, 2019)
Background: Conventional mapping techniques during atrial fibrillation (AF) are difficult to apply because of cycle length irregularity. Mapping studies are usually restricted to short durations of AF in limited regions because of the laborious manual annotation of local activation time (LAT). The purpose of this study was to test an automated algorithm to map activation during AF, with comparable accuracy to manual annotation. Methods: Left atrial (LA) mapping was performed using a 20‐pole double loop catheter (AFocusII) in 30‐second data segments from 16 patients. The new algorithm (RETRO‐Mapping) was designed to detect wavefront propagation between electrodes, and display activating wavefronts on a two‐dimensional representation of the catheter. Activation patterns were validated against their bipolar electrograms and with isochronal maps. The mapping protocol was approved by the research ethics committee (13/LO1169 and 14/LO1367). Results: During AF, uniform wavefront activation direction (mean ± SD, degrees) from manually constructed isochronal maps was comparable to RETRO‐Propagation Map (RETRO‐PM) and RETRO‐Automated Direction (RETRO‐AD): 1 ± 6.9 for RETRO‐PM; and 2 ± 6.6 for RETRO‐AD. There was no significant difference in activation direction assigned to 1373 uniform wavefronts during AF when comparing RETRO‐PM with RETRO‐AD (Bland‐Altman mean difference: −0.1 degrees; limits of agreement: −8.0 to 8.3; 95% CI −0.4 to 0.2; (r = 0.01) R2 = < 0.005; P = .77). Conclusion: We have developed and validated a new technique to map activation during AF. This technique shows comparable accuracy to that of conventional isochronal mapping with careful manual adjustment of LAT.